Peningkatan Kemampuan Pemahaman Matematika melalui Metode Pembelajaran Kooperatif Tipe STAD (Student Teams Achievement Divisions) - Eka Firmansyah (LPPM STKIP Kusuma Negara, 2016)
Attitudes and understanding of students' abilities can still be said to be unfavorable to the learning outcomes, especially in the Madrasah. One effort that can be done by teachers in improving student learning outcomes is to choose the model that suits the learning objectives to be achieved. One of the methods were deemed always effective and efficient in teaching is STAD cooperative learning method that emphasizes the activities and interaction among students to motivate each other, help each other to master the subject matter to achieve maximum performance. The purpose of this study was to determine 1) whether the ability of students to use mathematical understanding of cooperative learning is better than the ability of students to use mathematical understanding of conventional learning. 2) increase the quality of students' understanding of mathematics skills using cooperative learning and conventional learning 3) whether the student has a good attitude towards learning mathematics using cooperative learning. 4) increase the quality of students' understanding of mathematics abilities seen from the attitude of students using cooperative learning STAD 5) the effectiveness of the learning is done in this study. The method used in this study is experimental methods. The instrument used in this study is the ability of understanding the math test and attitude scale. Where the research population in MTsS Alif Al-Ittifaq class VIII with a randomly selected sample of the class VIII-A and VIII-B